Pengaruh Penempatan Pegawai terhadap Kinerja pegawai pada Kantor Dinas Perhubungan Kota Sorong - James Kastanya; Clan, Edward; Erubun, Josefina (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to analyze the impact of employee placement on employee performance at the Department of Transportation Office of Sorong City. The data analysis method used is quantitative, with significance testing (t-test) through linear regression. The research was conducted at the Department of Transportation Office of Sorong City with a sample size of 67 respondents. Primary data were collected through interviews, questionnaires, and documentation studies. Based on the results of a simple linear regression analysis processed using SPSS for Windows version 25, the Coefficient of Determination (R square) was found to be 51.6%. This indicates that employee placement contributes 51.6% to employee performance, while the remaining 48.4% is influenced by other factors not discussed in this study, such as career development. From the t-test results, it was found that the calculated t-value is 8.323, which is greater than the table t-value of 1.666, indicating that the employee placement variable has a positive and significant effect on employee performance.